"Good Enough" Security: The Best We'll Ever Have. - Hurlburt, George (Computer (00189162), 2016)
Given that no system is completely immune from attack, cybersecurity advances, while important, should take a backseat to improving human awareness of security risks. An objective, consensus-based rating system is one means to achieve this end.